2001
DOI: 10.1055/s-2001-17277
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity Profile of High-Performance Fencers

Abstract: There are only very few data available about the morbidity of elite fencers athletes. The aim of this study was to elucidate the nature and history of the morbidity in high-performance fencers. The injury profile over 15 years of 93 fencers at a highly competitive level was analysed by clinical assessment and examination. We found a positive correlation between the injured upper extremity with the dominant fencing side while the lower extremity showed no side preference with regard to vulnerability. Achillodyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Resulted from this dynamic and repetitive movements in fencing matches, fencing injuries were quite prevalent among the athletes. In spite of the rare cases of severe trauma caused by penetration (puncture by broken blades, account for 2.7–3.2%) [ 2 , 8 ], most of the fencing injuries arise from overuse. In a 5-year survey by the USFA [ 2 ], 184 cases of time-loss injuries were recorded for 610 exposures with an overall 30.0% of injury rate.…”
Section: Introductionmentioning
confidence: 99%
“…Resulted from this dynamic and repetitive movements in fencing matches, fencing injuries were quite prevalent among the athletes. In spite of the rare cases of severe trauma caused by penetration (puncture by broken blades, account for 2.7–3.2%) [ 2 , 8 ], most of the fencing injuries arise from overuse. In a 5-year survey by the USFA [ 2 ], 184 cases of time-loss injuries were recorded for 610 exposures with an overall 30.0% of injury rate.…”
Section: Introductionmentioning
confidence: 99%
“…We noted that male sabre and foil fencers displayed a higher annual injury rate than that noted for female fencers. German female fencers were previously reported to have an injury rate three times higher than that noted in their male counterparts, but no statistical analysis was carried out 8. The discrepancy between the findings in Korean and German fencers is most likely related to differences in training methods, physical build and style of play.…”
Section: Discussionmentioning
confidence: 90%
“…Such sudden movements can lead to overextension of joints, which carries a high risk of pulling muscles in the arms, legs and back,25 as well as a risk of injury resulting in ligament and muscle damage. While injury to the lower back is very common in all sports,8 29 fencers may experience it as a combination of concomitant conditions such as sacroiliac joint syndrome, hamstring injury and abdominal strain. Furthermore, we found that the distribution of affected body regions is different for each weapon category, which is in line with previous reports29 and can be explained by the different dynamics and skill sets required for performance in each weapon category, as well as the specific competition time and training methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the minimum fitness levels required to begin participating in this sport are relatively high – endurance, flexibility and strength levels at or just below average and coordination levels above average (Table 1). In addition, as this sport is associated with high rates of knee‐joint overloading and haematomas [16], fencing is not recommended for patients with haemophilia.…”
Section: Applying the Five‐item Fitness Check To ‘Real‐world’ Sportsmentioning
confidence: 99%